Electro-mechanical braking system development and hybrid electric vehicle power management for urban driving - Wei, Zhen (2018)
As the energy and environment crisis increase severely, developing cleaner and more fuel efficient vehicles have become a research hot spot of automobile industry. In recent years HEV (hybrid electric vehicle) and EV (electric vehicle) are widely considered as two of the most viable solutions to the world’s need for cleaner and more fuel-efficient vehicles.